153k views
0 votes
(3.2 * 10000000) -3

(3.2 * 10000000) -3-example-1
User Koroslak
by
5.0k points

1 Answer

5 votes

The exponents distribute over factors:


(ab)^c = a^c * b^c

so, you have


(3.2 * 10^6)^(-3) = 3.2^(-3) * (10^6)^(-3)

Let's focus on each factor: applying the definition of negative exponents, you have


3.2^(-3) = \cfrac{1}{3.2^3} \approx 0.03

While for the power of 10, you can use the following rule


(a^b)^c = a^(bc) to write


(10^6)^(-3) = 10^(6\cdot (-3)) = 10^(-18)

So, the expression evaluates to


0.03* 10^(-18) = 3* 10^(-20)

User Nizar Grira
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.